Carbon Tax Perspectives in Ukraine: Legal Regulation and Comparison of the National and European Experience of Implementation - Romanko, Svitlana (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
Environmental tax in general is one of the state's instruments in environmental protection and financing of the environmental protection measures. The purpose of the tax is to encourage business entities to reduce emissions / discharges of pollutants into the air / water bodies, to establish direct dependence of the amount of tax deductions on the degree of negative impact on the environment, mobilization of funds to budgets of different levels in order to finance the costs of protection and rational use of natural resources. This article examines and compares with Ukraine and EU countries the experience, rates and background policies of the carbon taxation. The carbon tax as an environmental tax with a significant effect on economic and legal incentives for business entities and state authorities to fulfill the policy of energy efficiency, energy saving and energy transition to renewable energy sources what is coincided with the mitigation of greenhouse gas emissions and achievement of National Determined Contributions according to the Paris Agreement and Kyoto Protocol. The main issue is that rate of carbon tax, used nowadays in Ukraine is not being sufficient to provide the energy transition of country economy to the less consuming model according the examples from Germany, Netherlands, Finland and other countries of Europe. Interconnected linkage between carbon tax, energy and climate policy is proven in the article along with mechanisms of economic, political and environmental peculiarities and benefits of the carbon taxation regulation improvement in national legislation